Isolation of Early Hematopoietic Stem Cells from Murine Yolk Sac and AGM - Morgan, Kelly (MyJove Corporation, 2008)
In the mouse embryo, early hematopoiesis occurs simultaneously in multiple organs, which includes the yolk sac and aorta-gonad-mesonephros region. These regions are crucial in establishing the blood system in the embryos and leads to the eventual movement of stem cells into the fetal liver and then development of adult stem cells in the bonemarrow. Early hematopoietic stem cells can be isolated from these organs through microdissection of the embryo followed by flow cytometric sorting to obtain a more pure population. It remains unclear how these stem cell populations contribute to the fetal and adult stem cell pool. Also, our lab investigates how early stem cells functionally differ from fetal and adult hematopoietic stem cells. Furthermore, our lab sorts different populations of hematopoietic stem cells and test their functional role in the context of a variety of genetic models. In this video, we demonstrate the micro-dissection procedure we commonly use and also show the results of a typical FACS plotfter isolating these rare populations, it is possible to perform a variety of functional assays including: colony assays and bone marrow transplants.